A166 SOFOSBUVIR-BASED THERAPY IN THE PRE-LIVER TRANSPLANT SETTING: THE CANADIAN NATIONAL EXPERIENCE. (1st March 2018) - Aljudaibi, B; Burak, K W; Yoshida, E M; Bilodeau, M; Wong, P; Benmassaoud, A; Hussaini, T; Thomas, B S; Chen, J; Teriaky, A; Marotta, P
Abstract: Aims: To assess the efficacy of SOF-based therapy in HCV infected transplant eligible patients and to evaluate decompensated liver disease patients with respect to changes that occur in liver function in the short term and the resultant effect on their liver transplant status Methods: A retrospective multicentre Canadian study of liver transplant candidates with advanced HCV cirrhosis treated with SOF-based therapy. Outcomes included sustained virologic response (SVR), changes in MELD-Na score, Child-Pugh score and liver transplant status Results: 96 liver transplant candidates with advance liver disease due to HCV were evaluated. 69 (71%) of patients have genotype 1, SVR was 88.3% (94% for G1, 68 % for non- G1). 49 patients were treated in the pre-assessment period and 47 patients were treated while awaiting transplantation. Of the 49 treated in the pre-assessment period, no significant difference in their average MELD-Na score (12 vs 12, p=ns) nor Child-Pugh score (7 vs 6 p=ns) occurred from baseline to SVR 12 date. However, among patients treated while wait listed for transplant, 14/47 (30%) remained active on the liver transplant list at the time of SVR12, 9/47 (19%) patients were delisted, 16/47 (34%) underwent liver transplantation. Progression of HCC lead to delisting of 1 and 8 deaths (1 after transplant) occurred. Among delisted patients, the average MELD-Na changed from 15 to 12 Conclusions: SOF-based therapy for patients progressing to liver transplantation leads to high SVR rates, short term stability in liver function, and in a sizable portion leads to delisting. These improvements may increase over time. Longer term follow up and further analysis is needed to understand the overall impact this will have on wait list deaths, number of transplants required for HCV and survival of non-HCV recipients. Funding Agencies: None